2011
DOI: 10.4103/1742-6413.85496
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-morphological features of extramedullary acute megakaryoblastic leukemia on fine needle aspiration and cerebrospinal fluid cytology: A case report

Abstract: Extramedullary deposits may be the presenting feature of acute myeloid leukemia. An early and accurate diagnosis on cytology will aid in correct patient management. This is especially true for patients with acute megakaryoblastic leukemia (AML M7), where bone marrow aspiration may yield only a dry tap. While cytomorphological features of myeloid sarcoma of other types are well recognized due to its rarity, there are only two case reports discussing the morphological details of megakaryoblastic differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In childhood AML cases, EML at diagnosis involved the orbits, skin and epidural sites . In addition to manifestations of obviously emergent EML ( e.g ., superior vena cava syndrome, pleural effusions, cord compression), sites of EML involvement requiring immediate attention have included the cerebrospinal fluid, small bowel, peritoneum, liver, pancreas and retroperitoneum . Authors reported cervical EML with postmenopausal bleeding and vaginal EML with urinary incontinence .…”
Section: Clinical Presentations Of Emlmentioning
confidence: 99%
“…In childhood AML cases, EML at diagnosis involved the orbits, skin and epidural sites . In addition to manifestations of obviously emergent EML ( e.g ., superior vena cava syndrome, pleural effusions, cord compression), sites of EML involvement requiring immediate attention have included the cerebrospinal fluid, small bowel, peritoneum, liver, pancreas and retroperitoneum . Authors reported cervical EML with postmenopausal bleeding and vaginal EML with urinary incontinence .…”
Section: Clinical Presentations Of Emlmentioning
confidence: 99%